Supporting Families, Empowering Children: A Randomized Controlled Trial on Social Inclusion - Laura Hospido; Bego\~na Varela (Institute of Labor Economics (IZA), 2025)
This paper evaluates a program that seeks to improve the levels of social inclusion of families with children and adolescents receiving the National Minimum Income Scheme (IMV) and/or the Regional Inclusion Income (RISGA) in the seven largest municipalities in Galicia, Spain. The intervention used stratified random assignment to evaluate the effectiveness of a new model of personalized and integral support, according to the specific needs of each member of the target family, with multiple interventions grouped into three packages (social, educational and labor). The control group received the usual financial aid from the traditional model. The analysis reveals that the treatment significantly reduces child material deprivation. Positive effects are also found in the synthetic indicator of social inclusion, with the greatest improvements concentrated in the measures of housing conditions, parental responsibilities, community integration, and education. The treatment, however, does not have a significant effect on simplified poverty indicators, on employability, or on income from work, despite an improvement in the activation of household members to search for employment.
Keywords: I32; I38; E24; C93; 330; social inclusion; families; children; randomized controlled trial